Kemampuan Berkomunikasi Guru Pendidikan Agama Islam terhadap Keaktifan Belajar Siswa di SMP - Hafiza, Nurul; Yanuarti, Eka; Meldina, Tika; Zulaiha, Siti (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research comprised two variables, communication ability of Islamic education subject teacher as X (independent) variable and student learning activeness as Y(dependent) variable. This research aimed at knowing whether there was a significantinfluence of communication ability of Islamic education subject toward student learning activeness at State Junior High School 1 Tanah Putih Tanjun Melawan, Rokan Hilir Regency. This research was a Correlation. The subjects of this research were all students. The teacher 2 of population all of the eighth-grade students class VII and VIII (243 students) and an Islamic education subject teacher were the population of this research, The sample is 1 teacher and 54 students. Proportionate stratified random sampling technique was used in this research. Questionnaire, observation, and documentation were used to collect the data. The technique of analyzing the data was Product moment correlation. SPSS 16.0 for Windows program was used to analyze the data. Based on the data analysis, there was a significantinfluence that the index obtained was 0.455 and rtable was 0.2681 at 5% significant level and 0.3477 at 1% significant level. It meant that robserved was higher than rtable, it could be described as 0.2681<0.455>0.3477. Thus, H0 was rejected and Ha was accepted. It meant that there was a significantinfluence of communication ability of Islamic education subject teacher toward student learning activeness at State Junior High School 1 Tanah PutihTanjungMelawan, RokanHilir Regency.